Remembering and ill health in postinvasion Kuwait: Topographies, collaborations, mediations - Casey, Conerly (Cambridge University Press, 2014)
Awakened by the pummeling blasts of nearby explosions, Dalia was unable to fall back asleep. Trembling, she crawled under her bed to hide, then ran to find her mother in the living room of their family’s home. Dalia knew immediately from her mother’s whispers and worried expression that Iraqi soldiers had invaded Kuwait. Dalia’s family, unlike many others who fled to neighboring or to European countries after the August 2, 1990, Iraqi invasion, remained in Kuwait during the seven-month occupation, covering their windows with blankets and sticky tape, little protection from the shattering glass of mortar explosions and gunfire. They talked their way past heavily armed Iraqi soldiers to search for food and water and, later, lived in sooty darkness, breathing in the residues of burning oil fires and other war contaminants.The 1990 Iraqi invasion and occupation of Kuwait led to highly mediated, emotionally charged ideas, images, and sounds of war, affective mediations of violence that continue to circulate. Less accessible to media audiences is the Harvard Schoolof Public Health (HSPH, 2005) finding that Kuwaitis, aged fifty years or older, who had remained in Kuwait for all or part of the occupation, were at 20–30 percent greater risk of mortality than those who fled the country. John Evans (2008; HSPH, 2005), director of theHarvard School of Public Health assessment of postinvasion health, suggested that smoke frommore than seven hundred oil fires burning from January to November of 1991 contributed to these higher mortality rates, though not in ways sufficient to cause the observed increases. After screening for “other contaminants – such as volatile organic compounds, polycyclic aromatic hydrocarbons and metals from the oil lakes and marine oil spills; and depleted uranium,” the HSPH (2005) team concluded that “exposures to these compounds were unlikely to lead to appreciable risks to public health.” The HSPH team, collaborating with Professor Jaafar Behbehani (Kuwait University Faculty of Medicine) and his colleagues at Kuwait’s Al-Riggae Specialized Centre (Hammadi, 1994), suggested instead that a combination of oil smoke and PTSD would explain the higher prevalence of mortality inthe fourteen years since independence (HSPH, 2005).
Created from Fastlane, Scopus look-up